CM Speeches for 55th NDC Meeting 24th July, 2010 Vigyan Bhawan New Delhi - Planning Commission (Planning Commission, 2010)
At the outset, I would like to convey my sincere thanks to the Government of India for convening the 55th Meeting of the National Development Council for the Mid-Term Appraisal of the 11th Five Year Plan (2007-12). I am happy that it is also slated to deliberate upon other important issues viz Urbanization, Strategy for Agriculture, Left-wing Extremism, Water Resources, Tribal Development, Interface between strategies for power generation and availability of coal etc.
Planning Commission
NDC Meeting